Citotoxicidad de las defensinas PaDef (Persea americana var. drymifolia) y γ-tionina (Capsicum chinense) contra la línea celular de cáncer de mama MCF-7 - Guzmán Rodríguez, Jacquelina Julia (Universidad Michoacana de San Nicolás de Hidalgo, 2016)
Cancer is a major health problem worldwide. In Mexico is the third cause of death, being the breast cancer one of the most prevalent. Conventional therapies have a low therapeutic index and severe side effects therefore alternative therapies are necessary. Antimicrobial peptides (APs) have been considered as promising anticancer agents because their ability to inactivate a wide range of cancer cells. The anticancer activities of APs include the lysis of cytoplasmic membrane and apoptosis induction. In this work, we assessed the cytotoxicity of plant APs PaDef (Persea americana var. drymifolia) and γ-thionin (Capsicum chinense) defensins against cancer cell line MCF-7 and we analyzed their mechanism of action. The PaDef defensin decreased the viability of MCF-7 cells in a concentration dependent manner showing an IC50 of 141.62 μg/ml. In addition, PBMC viability was unaffected but BMEC viability decreased. On the other hand, γ-thionin significantly inhibited MCF-7 viability with an IC50= 117.29 μg/ml. Interestingly, BMEC and PBMC viability was unaffected; suggesting that γ-thionin is selective to cancer cells. To determine the cytotoxicity mechanism of PaDef and γ-thionin on MCF-7 cells, we evaluated calcium efflux and membrane electrical potential. Both plant defensins did not modify these parameters, which indicate that the mechanism of these peptides on MCF-7 cells is not related to pore formation. On the other hand, both defensins increased the rate of apoptosis in a time-dependent manner reaching a maximum of 44 and 76%, respectively. To elucidate the apoptosis pathway induced by both plant defensins in MCF-7 cells, we evaluated the mitochondrial membrane potential (ΔΨm). Cells treated with PaDef and γ-thionin IC50 showed the loss of ΔΨm suggesting that intrinsic apoptosis has been activated.

El cáncer es un problema de salud importante a nivel mundial. En México es la tercera causa de muerte siendo el cáncer de mama uno de los de mayor incidencia. Las terapias convencionales tienen índices terapéuticos bajos y efectos secundarios severos por lo que es necesaria la búsqueda de nuevas terapias alternativas. Los péptidos antimicrobianos (PAs) son moléculas que han sido considerados una prometedora alternativa para tratar el cáncer debido a su habilidad para inactivar un amplio rango de células cancerosas. La actividad anticancerosa de los PAs incluye la lisis de la membrana citoplasmática y la inducción de apoptosis. En este trabajo se evaluó la citotoxicidad de las defensinas de plantas PaDef (Persea americana var. drymifolia) y γ-tionina (Capsicum chinense) contra la línea celular de cáncer de mama MCF-7 y se analizó su mecanismo de acción. La defensina PaDef disminuyó la viabilidad de las células MCF-7 de manera dependiente de la concentración, con una concentración inhibitoria 50 (IC50) de 141.62 μg/ml; las células PBMC no se vieron afectadas con la defensina, pero la viabilidad de las CEMB disminuyó por el tratamiento con la defensina PaDef (datos no mostrados). La defensina γ-tionina tuvo un efecto mayor sobre la viabilidad de las células MCF-7 respecto a PaDef, con una IC50 de 117.29 μg/ml; sin embargo, la viabilidad de las CEMB y PBMC no se vio afectada, sugiriendo que la γ-tionina es selectiva hacia las células cancerosas. Para determinar el mecanismo citotóxico de las defensinas PaDef y γ-tionina (IC50) se evaluó el daño a la membrana citoplasmática, el calcio extracelular y el potencial eléctrico de la membrana citoplasmática. Ninguna de las defensinas modificó estos parámetros, lo que sugiere que el mecanismo no está relacionado con la formación de poros.
Instituto de Investigaciones Agropecuarias y Forestales. Instituto de Investigaciones sobre los Recursos Naturales. Instituto de Investigaciones Químico Biológicas. Facultad de Biología. Facultad de Medicina Veterinaria y Zootecnia. Facultad de Químico Farmacobiología. Programa Institucional de Doctorado en Ciencias Biológicas
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/3699; info:eu-repo/classification/cti/6; FMVZ-D-2016-1028; Opción en biotecnología molecular agropecuaria; Cáncer; Aguacate; Chile habanero